FOOD CHOICE MOTIVES OF GENERATION Z IN SERBIA - Mitić, Sanja; Vehapi, Semir (Economics of Agriculture, 2021)
The topic of this paper is food choice motives of generation Z in Serbia. Generational cohort is used as a theoretical perspective, as the research is focusing on specific generational cohort. The aim of this research is to understand the characteristics of generation Z and their food choice motives. A Food Choice Questionnaire (FCQ) was used for analyzing generation Zs motives. A survey was used for data gathering. The sample consists of 287 students, from three universities from Serbia. The results are presented based on descriptive statistics, statistical testing and principal component analysis. The most important food choice motives identified are: sensory appeals, health and nutritional food attributes and convenience of preparation. The study revealed that generation Z in Serbia has some common features, as recognized in developed countries, but shows one interesting divergence, regarding the undervaluation of ethical factors. Managerial implications from the perspective of a marketing strategy are discussed.